Kiribati : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This Selected Issues paper focuses on recent developments with Kiribati's Revenue Equalization Reserve Fund (RERF). The paper also examines fiscal aspects of climate change, and considers options for improving fishing license fees, which remain an important source of revenue. It also analyzes recent developments and the outlook for remittances to Kiribati, which is another important source of external revenue and brings important economic benefits, such as reducing poverty and stabilizing national income.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet